2009
DOI: 10.1091/mbc.e09-06-0535
|View full text |Cite
|
Sign up to set email alerts
|

MICAL-L1 Links EHD1 to Tubular Recycling Endosomes and Regulates Receptor Recycling

Abstract: Endocytic recycling of receptors and lipids occurs via a complex network of tubular and vesicular membranes. EHD1 is a key regulator of endocytosis and associates with tubular membranes to facilitate recycling. Although EHD proteins tubulate membranes in vitro, EHD1 primarily associates with preexisting tubules in vivo. How EHD1 is recruited to these tubular endosomes remains unclear. We have determined that the Rab8-interacting protein, MICAL-L1, associates with EHD1, with both proteins colocalizing to long t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
246
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(257 citation statements)
references
References 38 publications
10
246
1
Order By: Relevance
“…Gene Knockdown by Silencing RNA (siRNA)-Custom design oligonucleotide duplexes targeting human EHD1 (Naslavsky et al (15)) and ON-TARGETplus SMARTpool siRNA targeting MICAL-L1 and Crmp2 (Dharmacon) were transfected for 72 h using Dharmafect (Dharmacon) as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene Knockdown by Silencing RNA (siRNA)-Custom design oligonucleotide duplexes targeting human EHD1 (Naslavsky et al (15)) and ON-TARGETplus SMARTpool siRNA targeting MICAL-L1 and Crmp2 (Dharmacon) were transfected for 72 h using Dharmafect (Dharmacon) as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence and Uptake Assays-HeLa cells were grown on coverslips, transfected with FuGENE 6 (Roche Applied Science), and fixed with 4% (v/v) paraformaldehyde as described previously (16). In some cases, cytosolic proteins were extracted by treatment for 1 min with 0.05% w/v saponin before fixation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Follow-up studies further suggested that Arf6 can recruit MICAL-L1 onto tubular endosomes, 30 suggesting that Arf6 can regulate Rab8 In mammalian systems, Rab35(GTP) recruits ACAP2/Arf GAP and thus regulates Arf6 activity. Rab35-mediated regulation of Arf6 via ACAP2 is important for NGF-induced outgrowth of neurite and phagocytosis.…”
Section: 28mentioning
confidence: 99%
“…8D, I). Integrins are known to be recycled through Rab11-, Rab8-and Rab4-dependent pathways (Bridgewater et al, 2012;Margadant et al, 2011;Sharma et al, 2009). To find an explanation why FA turnover and recycling of integrins in shR1 cells are increased (as shown in Fig.…”
Section: Reggie-1 Controls the Number Of Fas Via Rab11amentioning
confidence: 99%